First Report of Colletotrichum graminicola Causing Maize Anthracnose in Galicia, Northwestern Spain - Rogério, Flávia (Plant disease, 2023)
Maize (Zea mays) is one of the most important crops worldwide, and fungal diseases are responsible for major losses in food production. Anthracnose caused by Colletotrichum graminicola can infect all maize tissues, although stalk rot and seedling blight cause more significant economic damage (Munkvold and White, 2016). Anthracnose stalk rot is characterized by a distinctive external blackening of the lower stalks resulting in large black streaks, while the pith turns dark brown and has a shredded appearance. Like most stalk rots, the most obvious symptom is a sudden death of plants before grain maturity, and plant lodging. Symptoms commonly appear late in the season, suspicious maize stems of cultivar Tuy exhibiting symptoms of anthracnose stalk rot were collected from a field in Pontevedra, Galicia, Spain (Geographical coordinates: 42°23'27.1" N - 8°30'46.3" W) between June and December of 2022. Stem samples, approximately 50 mm2, were dissected and surface-disinfected for 90 seconds in 20% sodium hypochlorite (v/v) and rinsed three times in sterile distilled water. The samples were transferred to one half-strength acidified potato dextrose agar (PDA) supplemented with ampicillin (100 µg/mL) and lactic acid 90% (1.5 mL/L) and incubated for 5 days at 25 ºC (Sukno et al. 2008). Single spores were transferred to fresh PDA plates to obtain pure culture isolates. A total of six isolates were obtained, and among them, two were selected for further characterization (SP-36820-1 and SP-36820-3). Colonies grown on PDA have dark gray aerial mycelium with orange-colored spore masses. Conidia are falcate, slightly curved, tapered toward the tips, and are produced in acervuli with setae, measuring 37.65 to 24.84 x 8.02 to 4.67 µm, respectively (n = 100). These morphological characteristics are in agreement with C. graminicola previously described by Bergstrom and Nicholson (1999). Isolates were grown in potato dextrose broth (PDB) for 3 days at 25 ºC and total genomic DNA was extracted using a DNeasy Plant Mini Kit (Qiagen Inc., Valencia, CA, USA). The internal transcribed spacer region of rDNA and the manganese-type superoxide dismutase gene (SOD2) were amplified using primers ITS4/ITS5 (White et al. 1990) and SOD625/SOD507 (Fang et al. 2002) and consequently sequenced. GenBank BLAST analysis revealed that the sequences were 100% identical to strains of C. graminicola. All sequences were deposited in GenBank (see e-Xtra 1 for accession numbers). To confirm Koch's postulates, plants of a derivative of maize inbred line Mo940 (developmental stage V3) were placed horizontally in a tray for inoculation and 20 droplets (7.5 µL) of a suspension of 3 x 105 conidia per milliliter were placed on the surface of the third leaf. The trays were closed to retain moisture and incubated overnight at 23ºC. The next day, the plants were returned to a vertical position and incubated in a growth chamber at 25ºC with 80% humidity and a light cycle of 16 h of light and 8 h of dark (Vargas et al. 2012). After four days inoculated leaves presented brown elongated lesions with necrotic centers consistent with C. graminicola infection, whereas control plants remained asymptomatic. The strains reisolated from infected leaves were morphologically identical to the original isolates. To our knowledge, this is the first report of Colletotrichum graminicola causing maize anthracnose in Spain. Recently, maize anthracnose was also reported in Bosnia and Herzegovina and China (Duan et al. 2019; Cuevas-Fernández et al. 2019), suggesting the pathogen's geographic range is increasing, which may be a threat to maize cultivation in locations with optimal humid conditions for disease development